2020
DOI: 10.1002/jmv.26626
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of SARS‐CoV‐2 nucleocapsid protein and its consequences

Abstract: The emerged novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has created a global health crisis that warrants an accurate and detailed characterization of the rapidly evolving viral genome for understanding its epidemiology, pathogenesis, and containment. Here, we explored 61,485 sequences of the nucleocapsid (N) protein, a potent diagnostic and prophylactic target, for identifying the mutations to review their roles in real‐time polymerase chain reaction based diagnosis and obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 59 publications
7
99
0
Order By: Relevance
“…Impedance to form particular SR-motif due to RG KR mutation might disrupt the phosphorylation catalyzed by host glycogen synthase kinase-3 113 . Similar hypo- phosphorylation events could arise due to the conversion of serine to nonpolar or neutral amino acids (L 188/194/197 , I 193 , and N 202 ), as represented in supplementary Table S2 and 114 . Consequently, the low phosphorylation level after entering into the cell should unwind the viral ribonucleoprotein (RNP) in a slower but more organized fashion that might have an impact upon translation and immune-modulation 115117 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Impedance to form particular SR-motif due to RG KR mutation might disrupt the phosphorylation catalyzed by host glycogen synthase kinase-3 113 . Similar hypo- phosphorylation events could arise due to the conversion of serine to nonpolar or neutral amino acids (L 188/194/197 , I 193 , and N 202 ), as represented in supplementary Table S2 and 114 . Consequently, the low phosphorylation level after entering into the cell should unwind the viral ribonucleoprotein (RNP) in a slower but more organized fashion that might have an impact upon translation and immune-modulation 115117 .…”
Section: Resultsmentioning
confidence: 82%
“…This increasing contacts due to higher hydrogen bonds (Figure 5d) made the complex of mutated RdRp and NSP8 less flexible. Our analyses have identified that proline (P 323 ) or leucine (L 323 ) of RdRp can interact with the aspartic acid (D 112 ), cysteine (C 114 ), valine (V 115 ), and proline (P 116 ) of NSP8 (Figure 6). RdRp binds with NSP8 in its interface domain (residues alanine:A 250 to arginine:R 365 ), forming positively charged ‘sliding poles’ for RNA exit and enhance the replication speed probably by extending the RNA-binding surface on NSP8 88, 89 .…”
Section: Resultsmentioning
confidence: 98%
“…The binding of antibody to the antigen can be hindered if the antigenic epitope sequence gets a mutation, thereby compromising the detection sensitivity of the LFIA. Comprehensive genome analysis of 61,485 different sequences of SARS-CoV-2 NP genes revealed 1034 unique nucleotide mutations, with the most common substitution being R203K (68.09 %), followed by G204R (67.94 %) (Rahman et al, 2020). However, the none of these mutations were found in the binding region on NP of the two mAbs used in this study, implying that the YCU-FF LFIA can identify all the currently identified circulating mutants of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2's N (Nucleocapsid) protein is a putative RNA-binding protein responsible for gathering the viral RNA genome for encapsulation in the viral membrane into compact ribonucleoprotein (RNP) complexes [45]. N is the structural unit present in the nucleocapsid of the SARS-CoV-2 genome, 46 kDa protein and comprises of 419 amino acids (aa) containing three distinctly diverse domains: The N-terminal domain (NTD)/RNA-binding domain (46-174 aa), the serine/argininerich (SR-rich; 184-197 aa) linker region (LKR; 175-254 aa) and the C-terminal domain (CTD; 255-364 aa) (Figure 8) [46]. Both domains (NTD & CTD) are flanked by an inherently disordered region IDR, which is the central linker region (LKR) with a Ser/Arg (SR)-rich area containing alleged phosphorylation sites [47,48].…”
Section: Nucleocapsid (N)mentioning
confidence: 99%